Pengaruh Periode Penggunaan Tamoxifen Terhadap Kejadian Endometriosis Pada Penderita Kanker Payudara - Agreno, Marshal; Darmi, Noer Faisal; Ismy, Jufriady; Erdani, Ferry; Hidayat, Imam (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Tamoxifen (selective estrogen receptor) is the standard hormonal therapy in women with breast cancer with positive estrogen receptor. The use of this regimen proved to reduce the incidence of relapse at local, collateral, or distant body area, and also decrease breast cancer mortality. One of the effects of tamoxifen is to induce endometrial proliferation, cause various abnormalities in endometrial tissue.Method: This study is an unpaired categorical comparative analytic study with a retrospective single cohort (internal comparison group) design. All breast cancer patients at dr. Zainoel Abidin Banda Aceh from 2017 - 2019 was involved in this research. Evaluation of the incidence of endometriosis was carried out based on the duration of tamoxifen using the Mann-Whitney U test. This study is an unpaired categorical comparative analytic study with a retrospective single cohort (internal comparison group) design. All breast cancer patients at dr. Zainoel Abidin Banda Aceh from 2017 - 2019 was involved in this research. Evaluation of the incidence of endometriosis was carried out based on the duration of tamoxifen using the Mann-Whitney U test.Result: A total of 114 patients (46.15%) out of a total of 247 breast cancer patients using tamoxifen reported experiencing endometriosis with a mean age of 49 years old. Most of the patients diagnosed with stage IIIB breast cancer of ductal cell carcinoma. A total of 111 people (97.37%) experienced endometriosis after taking tamoxifen for 30-36 months and the remaining 3 (2.63%) after 24-29 months. The mean duration of tamoxifen use associated with endometriosis was 34 months (p less than 0.001).Conclusion: Long-term use of tamoxifen in breast cancer patients increases the risk of endometriosis